MRI‐Visible siRNA Nanomedicine Directing Neuronal Differentiation of Neural Stem Cells in Stroke. (5th February 2018) - Lu, Liejing; Wang, Yong; Zhang, Fang; Chen, Meiwei; Lin, Bingling; Duan, Xiaohui; Cao, Minghui; Zheng, Chushan; Mao, Jiaji; Shuai, Xintao; Shen, Jun
Abstract: A major challenge in stroke treatment is the restoration of neural circuit in which neuron function plays a central role. Although transplantation of exogenous neural stem cells (NSCs) is admittedly a promising therapeutical means, the treatment outcome is greatly affected due to the poor NSCs differentiation into neurons caused by myelin associated inhibitory factors binding to Nogo‐66 receptor (NgR). Herein, a nanoscale polymersome is developed to codeliver superparamagnetic iron oxide nanoparticles and siRNA targeting NgR gene (siNgR) into NSCs. This multifunctional nanomedicine directs neuronal differentiation of NSCs through silencing the NgR gene and meanwhile allows a noninvasive monitoring of NSC migration with magnetic resonance imaging. An improved recovery of neural function is achieved in rat ischemic stroke model. The results demonstrate the great potential of the multifunctional siRNA nanomedicine in stroke treatment based on stem cell transplantation. Abstract : A magnetic resonance imaging (MRI)‐visible nanocarrier based on a cationic polymersome is constructed. The nanocarrier complexes siRNA in its cationic membrane and transfects NSCs effectively, resulting in remarkably enhanced neuronal differentiation of exogenous neural stem cells (NSCs) by downregulating the Nogo‐66 receptor expression to promote functional recovery in acute ischemic stroke. Moreover, the MRI‐visible nanomedicine shows advantage of providing noninvasive imaging of NSC migration and homing.